THE TRAUMA OF BLACK WOMEN IN BESSIE HEAD’S SELECT NOVELS - Kumar, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Before Nelson Mandela came to power in South Africa, the country's literature was basically a protest against the dehumanizing treatment of Black people by the White minority who controlled the country under the apartheid doctrine. This somehow led to a pervasive environment and socio-political instability. As a result, some authors set out to propose an ideal society for humanity while deciphering this social mystery. Bessie Head is one of them. This essay aims to analyse Head's When Rain Clouds Gather and Maru in order to show how her personal experiences and the dystopian South African society have influenced her desire for the ideal society.